A Digest of the Statute Laws of Kentucky, of a Public and Permanent Nature, from the Commencement of the Government to the Session of the Legislature, Ending on the 24th February, 1834. With References to Judicial Decisions Page 788, Image 794 (Vol. 1, 1834) - (:unkn) unknown (General Publisher, 1834)
That whosoever shall hereafter use any fire-hunting or the killing of any deer by such means on any patented land, every person present at such fire hunting shall forfeit and pay twenty shillings for every such offense; and if any Indian be found fire-hunting as aforesaid, it shall and may be lawful for the owner of such land, or his or her overseer, to take away the gun of such Indian, and the same to keep to his own use.
--
Keywords: HUNTING REGULATION